Ночь, когда она исчезла: [роман] / Лайза Джуэлл ; [перевод с английского Т. Бушуевой] - Джуэлл Лайза (Эксмо, 2022)
Экземпляры: РБ (20230830) / Инвентарный номер: 66177 / Цена: 100.00 / Авт.знак: Д 42 / ГРНТИ: 17.82 / ББК: 84(4Вел)